Integrative Strategies for Cardiovascular Risk Reduction: Synergy between Lifestyle Modifications and Pharmacotherapy - Mstowska, Weronika; Byjoś, Ewa; Zbylut, Mateusz; Bury, Karolina; Fabiś, Katarzyna; Milewska, Kamila; Buczek, Sylwia; Mateja, Patrycja; Naliuka, Hanna; Młynarczyk, Katarzyna (Quality in Sport, 2026)
Background: Cardiovascular diseases (CVD) remain the leading cause of mortality worldwide, primarily driven by atherosclerosis. Dyslipidemia, characterized by elevated atherogenic lipoproteins, represents a key modifiable risk factor in both primary and secondary prevention. Objective: This narrative review synthesizes current evidence on the integrative management of dyslipidemia, emphasizing the combined role of lifestyle modifications: physical activity, dietary patterns, weight management and established and emerging pharmacological therapies. Methods: A narrative review of European Society of Cardiology (ESC) and European Atherosclerosis Society (EAS) guidelines, as well as peer-reviewed literature, was conducted. The analysis focused on lipid metabolism, nutritional strategies, physical activity, and lipid-lowering therapies ranging from statins to novel siRNA-based agents. Results: Lifestyle interventions are the foundation of cardiovascular prevention. Regular physical activity (150–300 min/week) and weight reduction in obesity lead to meaningful improvements in lipid profiles. Dietary modifications, particularly reducing saturated fats and improving fat quality, contribute to lowering LDL-C and triglyceride levels. In patients at high or very high cardiovascular risk, lifestyle measures alone are frequently insufficient, necessitating pharmacotherapy, primarily statins, with add-on agents such as ezetimibe, PCSK9 inhibitors, or inclisiran to achieve lipid targets. Conclusion: A comprehensive strategy integrating sustained lifestyle modification with intensified pharmacotherapy provides the greatest reduction in CVD risk. Understanding the synergistic effects of these interventions may improve long-term adherence and overall treatment effectiveness.